Explicit and reflective teaching for the development of Critical Thinking skills and Nature of Science and Technology understandings in Primary Education - Vanessa Ortega-Quevedo; Cristina Gil-Puente; Cristina Vallés Rapp; Carmela García-Marigómez (Investigações em Ensino de Ciências)
This study seeks to contribute to the development of critical thinking (CT) skills and nature of science (NOS) concepts in primary education – more specifically, argument analysis (CT) and certain aspects of the external sociology of science, such as scientific decision making and the compromise between the positive and negative effects of science and technology (NOS). The study involved the participation of 72 students from 5 different schools. It was a mixed-design study, using tools such as questionnaires, observation charts and interview scripts. The results showed significant improvement in argument analysis questionnaire scores and in NOS concepts after the explicit and reflective work done in a teaching-learning sequence. These results were confirmed by classroom observation, the analysis of workbooks and student interviews within a month of the intervention. This enabled us to conclude that the intervention had a positive impact on the development of the skills and concepts under study, even in the face of variation as a result of differences in teaching-learning sequence implementation by different teachers in different contexts. The reflective teaching approach can be identified as one of the keys to intervention success.